2018
DOI: 10.1161/jaha.118.008939
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial‐Mediated Oxidative Ca 2+ /Calmodulin‐Dependent Kinase II Activation Induces Early Afterdepolarizations in Guinea Pig Cardiomyocytes: An In Silico Study

Abstract: BackgroundOxidative stress–mediated Ca2+/calmodulin‐dependent protein kinase II (CaMKII) phosphorylation of cardiac ion channels has emerged as a critical contributor to arrhythmogenesis in cardiac pathology. However, the link between mitochondrial‐derived reactive oxygen species (mdROS) and increased CaMKII activity in the context of cardiac arrhythmias has not been fully elucidated and is difficult to establish experimentally.Methods and ResultsWe hypothesize that pathological mdROS can cause erratic action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the increased cytosolic Ca 2+ levels can lead to mitochondrial Ca 2+ overload, further increasing ROS production and ultimately resulting in cell death (Figure 2) (Gambardella et al, 2017). It has been shown that oxidative CaMKII activation leads to after depolarization's in isolated rabbit cardiomyocytes, caused by phosphorylation of L-type Ca 2+ (LTCC) and Na + channels (Yang et al, 2018). In addition, mitochondrial-targeted antioxidant treatment has shown to suppress early after depolarization's (EADs) in an in silico model of guinea pig cardiomyocytes (Yang et al, 2018).…”
Section: Calcium/calmodulin-dependent Protein Kinase II Activation Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increased cytosolic Ca 2+ levels can lead to mitochondrial Ca 2+ overload, further increasing ROS production and ultimately resulting in cell death (Figure 2) (Gambardella et al, 2017). It has been shown that oxidative CaMKII activation leads to after depolarization's in isolated rabbit cardiomyocytes, caused by phosphorylation of L-type Ca 2+ (LTCC) and Na + channels (Yang et al, 2018). In addition, mitochondrial-targeted antioxidant treatment has shown to suppress early after depolarization's (EADs) in an in silico model of guinea pig cardiomyocytes (Yang et al, 2018).…”
Section: Calcium/calmodulin-dependent Protein Kinase II Activation Bymentioning
confidence: 99%
“…It has been shown that oxidative CaMKII activation leads to after depolarization's in isolated rabbit cardiomyocytes, caused by phosphorylation of L-type Ca 2+ (LTCC) and Na + channels (Yang et al, 2018). In addition, mitochondrial-targeted antioxidant treatment has shown to suppress early after depolarization's (EADs) in an in silico model of guinea pig cardiomyocytes (Yang et al, 2018). Phosphorylation of Na V 1.5 delays the I Na recovery time after inactivation and enhances the persistent late Na + current (Wagner et al, 2006).…”
Section: Calcium/calmodulin-dependent Protein Kinase II Activation Bymentioning
confidence: 99%
“…Growing evidence has further indicated the importance of mitochondrial Ca 2+ in arrhythmogenesis [ 140 ]. Mitochondrial ROS production induces RyR2 oxidation [ 141 ] and/or oxidative activation of Ca 2+ /calmodulin-dependent protein kinase II [ 142 ], leading to mitochondrial Ca 2+ overload that contributes strongly to arrhythmogenesis in cardiac pathology.…”
Section: Molecular Mechanisms Underlying Burn-impaired Cardiac Mitmentioning
confidence: 99%
“…Xie et al (2009) have showed that H 2 O 2 perfusion-induced oxidative CaMKII activation leads to afterdepolarizations in isolated rabbit cardiomyocytes, likely via phosphorylation of Na + channels and LCCs. In a computational study, Yang R. et al (2018) reported that mdROS-mediated oxidative CaMKII activation induces EADs in guinea pig cardiomyocytes by enhancing the late component of Na + current. The proarrhythmic role of CaMKII oxidation in diabetic hearts has been demonstrated in a recent study showing that selective genetic blocking of CaMKII oxidation prevents the enhanced atrial fibrillation (AF) risk (Mesubi et al, 2017), which has been implicated to be associated with increased mortality in response to myocardial infraction (Luo et al, 2013).…”
Section: Mitochondrial-associated Cardiac Arrhythmiamentioning
confidence: 99%